THE EFFECT OF TAX BURDEN AND TUNNELING INCENTIVE ON TRANSFER PRICING (Empirical Study on All Multinational Companies Listed on the Indonesia Stock Exchange for the 2019–2023 Period) - Yohana Eka Putri Saralisa; Made Gede Wirakusuma (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the effect of tax burden and tunneling incentive on transfer pricing practices in multinational companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The study is based on 163 observations from 34 multinational companies selected using purposive sampling. Transfer pricing is measured using the ratio of total related party transactions (RPTAL), while the tax burden is proxied by the effective tax rate (ETR), and tunneling incentive is proxied by ultimate ownership. This study applies stakeholder theory to explain the influence of external pressure from stakeholders, particularly tax authorities, on corporate policies regarding transfer pricing. Panel data regression analysis is conducted using the random effect model (REM). The results show that the tax burden has a significant effect on transfer pricing, indicating that the higher the tax burden, the greater the tendency for companies to engage in transfer pricing. Meanwhile, the tunneling incentive has no effect on transfer pricing, suggesting that large ownership stakes do not necessarily encourage transfer pricing practices in multinational companies. Companies’ responses to fiscal pressure indicate a tendency to optimize through transfer pricing strategies to minimize tax burdens and maintain financial performance. Nevertheless, such decisions still take into account trust, governance, and oversight from other stakeholders.